IMPLEMENTASI PENDIDIKAN KARAKTER PADA MATA PELAJARAN PENDIDIKAN KEWARGANEGARAAN DI SD - Thalita Nailah Putri; Awiria (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the implementation of character education in Civic Education (PKn) learning in Elementary Schools. Civic Education (PKn) in Elementary Schools. Character education integrated into the subject of PKn has an important role in shaping students' attitudes and behaviors according to moral, social, and national values. The method used is a systematic literature review (SLR) to obtain an overview and data on the variables studied explicitly, structured, and accountable. Data sources come from scientific papers such as journal articles, books, notes, and relevant reports. The results of the study indicate that the implementation of character education in PKn in elementary schools is running well and has a positive impact on the development of students' attitudes and behaviors. The Learning Implementation Plan (RPP) prepared by teachers specifically integrates character values ​​such as tolerance, discipline, responsibility, and honesty. The use of creative learning media, such as pictures, videos, and educational games, can increase students' interest and understanding of PKn material and the character values ​​taught. Parental support is also an important factor that strengthens the process of forming students' character.